2022
DOI: 10.3390/ijerph19053060
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Stress of Work from Home with Housemates Based on Residential Types

Abstract: The COVID-19 pandemic has had a significant impact on work environments. Many workers have been requested or instructed to work from home (WFH). This study aimed to clarify the work-related stress of WFH regarding housemates based on residential types during the COVID-19 pandemic. We conducted a web-based questionnaire survey of 500 workers living with housemates in Osaka Prefecture. The WFH environments were analyzed on the basis of high-stress workers (HSWs), which accounted for 17.4% of all subjects, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
6
2
1
Order By: Relevance
“…Interference from noise or odor was significantly associated with high psychosomatic symptoms. A previous study during the COVID‐19 pandemic among Japanese workers working from home reported that workers with housemates showed high‐stress reactions if the noise from housemates interfered with their work 3 . In our study, the item related to family members did not show a significant association with outcomes.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Interference from noise or odor was significantly associated with high psychosomatic symptoms. A previous study during the COVID‐19 pandemic among Japanese workers working from home reported that workers with housemates showed high‐stress reactions if the noise from housemates interfered with their work 3 . In our study, the item related to family members did not show a significant association with outcomes.…”
Section: Discussioncontrasting
confidence: 85%
“…Poor environmental factors can influence employees' mental health. Previous studies examined factors such as noise at home, 3 lightning at the office, 4 and poor air quality in an experimental environment 5 . Lack of acoustic and visual privacy, inadequate thermal conditions, and lack of control over various environmental factors decreased employees' environmental satisfaction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Iako rad licem u lice ima svoje prednosti, kao što je laka i efikasna komunikacija, on takođe ima i nedostatke, kao što je neprijatnost ograničenosti prostorom i vremenom, kao i stresom zaposlenih koji je vezan za putovanje na posao. Široka upotreba širokopojasnih veza i računara kao i audio i vizuelnih interfejsa učinila je daljinsku komunikaciju prihvatljivom bez interakcije licem u lice (Natomi et al, 2022). U početku, nekim osobama može predstavljati problem da razdvoje lični i poslovni život kada ne odlaze u kancelariju i da uspostave ravnotežu, ali postoje tehnike koje omogućavaju lakše razdvajanje ove dve sfere (DiNardi, 2022).…”
Section: Uticaj Pandemije Na Organizacione I Komunikacione Aspekte Za...unclassified
“…Recent studies reported positive and negative outcomes of WFH in different home working arrangements and home conditions [ 15 , 16 , 17 , 18 ]. On the positive side, at the personal level, studies reported lower time pressure [ 19 ], better control of work schedules [ 17 ], higher work motivation [ 20 ], higher life satisfaction [ 21 ], and less work-family conflict [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the negative side, teleworkers perceived lower subjective well-being [ 18 , 23 ], lower psychological well-being [ 24 ], negative relationships with co-workers [ 17 ], and conflict within the organization [ 25 ]. Teleworker stress level results have been controversial because some teleworkers reported higher stress levels [ 16 , 18 , 23 , 24 , 25 ], whereas others reported lower stress levels [ 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%